A customer methodology for developing green cellular phone: a case of University Malaysia Pahang Students - Uddin, Mueen; Chand, Roop; Shah, Asadullah (2015)
economic and Environmental Eco-design of mobile phones is considered as promising; However in customer marketplace it is still ineffectual. Inadequate eco-design of green phones determines the lack of customer voice and participation for product development and design in the marketplace. The main impediment is that, many organizations are asked to formulate and present their designs that support environmental green mobile phones characteristics and features but these organizations are not sufficient enough to recognize their voice in the planning and design phase of product development. The research proposed in this paper fills the gap between wispy customers perspective and designer's approach for developing green mobile phones. This research emphasizes on costumer-influenced criteria and features for green mobile development by reflecting green mobile phone definition and uses quantitative approach as a tool of analysis performed to prove how customer participation can improve the overall green mobile phone design. The research is performed at University Malaysia Pahang where suggestions from different students and staff and other employees were statistically analyzed to prove that customer voice and involvement is really important and major factor for developing green Eco-friendly mobile phones.